Tauhid Education in Pesantren (Study of Tauhid Thought and Education in Pesantren al-Mukmin Ngruki, Central Java, Indonesia) - Din Muhammad Zakariya (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This research aims to reveal the thoughts possessed  by the kyais and ustadz in Pesantren al-Mukmin on the tauẖîd education, and their implementation. The method used in this reseach was qualitative. The results of this research are as follows. Firstly, tauẖîd is given  a special attention since the main aim of education in the pesantren al-Mukmin Ngruki is to produce  a muslim generation with pure tauẖîd coloring all their lives. KH. Wahyudin and ustadz Abdurrahim Ba’asyir Lc understand tauẖîd in line with Ibnu Taimiyah and Muhammad bin Abdul Wahab. Secondly, Tauẖîd education in Pesantren al-Mukmin Ngruki using three methods of education; the doctrine of tauẖîd values, understanding, and practice. Meanwhile the learning of tauẖîd in the Pesantren al-Mukmin Ngruki more adopted the concept of tauẖîd proposed by Muhammad bin Abdul Wahab and Ibn Taimiyah since the books studied in the ẖalaqah program are written by Muhammad bin Abdul Wahab, while those studied in the learning of tauẖîd in the class are written by Dr. Shalih Fauzan who is one of the figures in the Muhammad bin Abdul Wahab tauẖîd dakwah movement in Saudi Arabia.  Kata kunci: Tauẖîd, Education, Pesantren